‘Do we still need the CIA?’ Daniel Patrick Moynihan, the Central Intelligence Agency and US foreign policy - McGarr, Paul M. (Wiley, 2015)
In May 1991, writing in the op-ed column of the New York Times, the US Senator for New York, Daniel Patrick Moynihan, called for the Central Intelligence Agency to be disbanded. Arguing that the CIA represented an historical anachronism that had outlived its usefulness to American foreign policy-makers, Moynihan proposed that the Agency should be stripped of its autonomy and have its intelligence functions subsumed by the Department of State. Moynihan's rhetorical assault on the CIA marked the opening salvo in a protracted campaign that, over the following decade, until his death in March 2003, would see the one-time member of the Senate Select Committee on Intelligence lobby relentlessly for reform of America's intelligence community and against pervasive official secrecy. To date, Moynihan's evangelical fervour in championing a more open intelligence paradigm, which came to incorporate the drafting of congressional bills, the chairmanship of a bipartisan commission on government secrecy, the publication of a book, and innumerable speeches and articles, has been interpreted in a narrow personal and political context. Commentators have tended to characterize Moynihan's turn against the CIA, and towards government transparency as symptomatic of individual eccentricity, disenchantment with purported Agency excesses during the Reagan administration, and ill-judged post-Cold War hubris. This article breaks new ground by reframing and reperiodizing Moynihan's relationship with intelligence. It suggests that Moynihan's attitudes to intelligence and state secrecy were formulated much earlier than has hitherto been acknowledged, and in an environment far removed from Washington's corridors of power. Specifically, the essay relocates Moynihan's emergence as an advocate of intelligence reform in the global political turmoil of the early 1970s when, as Richard Nixon's ambassador to India, he was afforded ample scope to assess the CIA's utility as an instrument of American diplomacy.